Czy Juwenalis nienawidził Egipcjan? Problemy interpretacyjne "Satyry XV" = Did Juvenal hate the Egyptians? Interpretation problems of "Satire XV" - Hołubowicz, Karolina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Juvenal`s "Satire XV" is a complex poetic work causing difficulties in interpretation. Mistakes are often made while interpreting it, such as identifying the author with the lyrical subject or interpreting his words directly, without taking into account numerous treatments occurring in the text such as irony, paradox or references to other pieces of literature.
Keywords: Juwenalis (poeta rzymski; 60-130); satyra; kanibalizm; Egipcjanie; Rzymianie; poezja; satire; cannibalism; Egyptians; Romans; poetry